Prevalence of early childhood caries in 8 - 48 month old preschool children of Bangalore city, South India - Priya Subramaniam; P Prashanth (Wolters Kluwer Medknow Publications, 2012)
Early Childhood Caries (ECC) is a devastating form of dental decay having a multi - factorial origin. This study was undertaken to determine the prevalence of ECC in Bangalore city, South India, and also to study its associated risk factors. Random sample of 1500 children, aged between 8 - 48 months, was selected from play homes and nursing homes of various parts of the city. Dental caries was recorded according to World Health Organization criteria. Information regarding risk factors for caries was obtained through a structured questionnaire given to mothers or caretakers. The data was subjected to statistical analysis. The prevalence of ECC was 27.5% and the mean decayed, extracted and filled tooth index was 0.854. There was a strong association of ECC with the risk factors studied.